SOSIOLOGI GENDER: Poligami Perspektif Hukum Islam - Ahmad Muzakki (LP2M Universitas Ibrahimy, 2016)
Polygamy has been a debate among some scholars of Islam about whether or not to allow it.After investigation, the actual points of that debate can be found in the practice of polygamy that happen in society. Gender activists who disagree and opposed poligamy actually oppose the practice of polygamy that opposes polygamy lies in the practice of polygamy that oppressdespoticalyto women.Hence the verse about the permissibility of polygamy should not be deprived to legalize the satisfication of the sexual libido of mens.Otherwise, thatverse should be placed in the study of sharia law that releases with no disregard the historical aspects of the practice of polygamy which is exemplified by the Prophet.With this perspective, the dimensions of morality in the verse of polygamy become the central point for consideration,because, the law without ethics is a wicked, and ethics without law is justutopia that far from harmonious and desirable social regulation building.Necessarily Muslims, who want to polygamy, not only follow the Sharia law but also followthe regulations of law that applied in Indonesia.Â